International comparison of light rail operations with reference to urban population density patterns - Graham Crampton (European Regional Science Association (ERSA), 2001)
The experience of urban light rail in Europe offers sharp contrasts. The German and French experience has placed light rail or tram at the centre of attempts to revitalise city centres using attractive modern forms of new public%0D transport infrastructure. British experience has been based on a closer focus on value for money and tighter limits to subsidy, at both the infrastructure and operation stage. With this policy contrast as a background, this paper reports on an international research project which used GIS techniques to map light rail routes and local population density patterns for a selection of case study cities. It addresses issues such as whether specific modern tram systems such as the Sheffield Supertram was handicapped by decisions over its routing%2C together with the scale of international differences in local population densities and their impact on accessibility of the population to the light rail system. The project made use of local authority data from German, French, and British cities, plus analysis using MapInfo GIS software.
Keywords: 330